Raumplanung in Deutschland und Polen – eine rechtsvergleichende Skizze - Geis, Max-Emanuel; Frank, Kevin (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Spatial planning in Germany and Poland has a long history. In addition to individual spatial planning, there are also joint as well as general European approaches to the use of space. The article first shows the legal framework at national and supranational level, followed by an in-depth presentation based on several projects from the energy and infrastructure sectors. Finally, the similarities and differences are worked out.
Keywords: similarities; offshore wind farms; nuclear power station; autostrada A1; central airport